Assessing the effects of cornerstone reading tutorial - Gaoiran, Mirasol; Hormillada, Christine C; Evardo, Mae A; Mante, Katrine Mae B; Naquila, Angelie S (American Journal of STEM Education, 2026)
Reading is a vital skill that shapes students’ academic performance across all subjects. This study examined the impact of a reading intervention on the proficiency and English performance of Calape Central Elementary School students from 2016 to 2018. Implemented through the collaboration of Bohol Island State University–Calape Campus, Couples for Christ–ANCOP, and the Department of Education, the program used a quantitative design with 59 slow readers from the 4th and 5th batches. Data were gathered through the Dolch Basic Sight Vocabulary Test and English grades, analyzed via correlated t-test. Results showed a 27.65% improvement in reading and a 1.57% increase in grades. Findings confirm the program’s effectiveness, recommending its continued expansion through collaborative partnerships.